From State-Centric to Security Complexes: A Review of Regional Security Complex Theory in International Relations - Farzayee, Shafiullah (Department of Political Science - Universitas Sains Al-Qur’an, 2023)
Regional Security Complex Theory (RSCT) has gained prominence as a valuable framework for analyzing the complex interplay of security interactions within and across regions. This literature review comprehensively examines the theoretical underpinnings, historical development, applications, empirical validation, and future directions of RSCT. RSCT offers a holistic approach that transcends traditional state-centric perspectives, encompassing non-state actors, sub-regional dynamics, and geographical factors in shaping security landscapes. It has been successfully applied to analyze regional security complexes in diverse regions, including Europe, Asia, the Middle East, and Africa. Empirical studies have supported the validity of RSCT, but further rigorous testing is needed to refine the theory and enhance its predictive power. As the global security landscape evolves, RSCT remains an essential tool for understanding and anticipating the intricate dynamics of regional and global security challenges. This paper proposes that the future research should focus on refining RSCT's conceptual framework, exploring interactions between RSCs, examining the role of non-state actors and regional institutions, and integrating RSCT with other theoretical frameworks in international relations.